Analisis Sistem Sanitasi Lingkungan melalui Penatalaksanaan Jamban Keluarga dan Drainase Lingkungan (Studi Kasus: Kawasan Kumuh Kelurahan Campago Ipuh Kota Bukittinggi) - Ulfa, Iftinan Fatihah; Chandra, Deded (Lembaga Yasin AlSys, 2025)
Poor environmental sanitation is one of the main indicators of slums and has a significant impact on public health. This study aims to analyze (1) the condition of the availability of quality family latrines in the slum area of Campago Ipuh Village, Bukittinggi City, and (2) the impact of poor environmental sanitation conditions on public health in the area. The study used a quantitative descriptive method with a population of 2,169 households, then a sample of 96 households was determined using the Slovin technique. Data collection was conducted through observation, primary survey using questionnaires, and interviews, while data analysis was conducted with the help of ArcGIS software. The results showed that the condition of the availability of quality family latrines and environmental drainage was dominated by private latrines and drainage that were classified as feasible, although drainage was still found that did not meet technical standards, as well as sanitation facilities that needed quality improvement. This condition shows that despite efforts to improve, the quality of sanitation in Campago Ipuh Village still has the potential to have a negative impact on public health. Therefore, it is necessary to improve sanitation infrastructure and strengthen clean and healthy living behaviors.